The level of development of the digital economy in Poland and selected European countries: A comparative analysis - Miroslaw Moroz (Foundations of Management, 2017)
An assessment of the degree of the development of the digital economy in Poland in comparison to chosen European countries is the main purpose of the paper. The methodology of the conducted research is based on the analysis of secondary sources and applying statistical methods. In order to make the comparison in methodically correct manner, synthetic measures of the development of the e-economy were used in the form of two indexes: NRI (Networked Readiness Index) and DESI (Digital Economy and Society Index). On the basis of available statistical data, four European countries were confronted with Poland. Results of the analysis indicate a relatively unfavorable situation of Poland.
Keywords: 650; Digital economy; comparative analysis; Poland; Slovakia; Germany; Lithuania; Italy; NRI; DESI